Low Power Active Electrode ICs for Wearable EEG Acquisition - Xu, Jiawei; Yazicioglu, Refet Firat; Van Hoof, Chris; Makinwa, Kofi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents fundamental requirements, electrical specification, and parameter tradeoffs of wearable EEG acquisition circuits, especially those compatible with dry electrodes for user-friendly recordings.  The authors introduce active electrode, the most promising solution for dry electrodes-based EEG measurement. This architectural concept has been combined with various, innovative circuit design techniques to illustrate structured IC design methodologies for high performance EEG recording. This book also gives examples on the design, implementation and evaluation of three generations of active electrode ICs.
Chapter 1.Introduction -- Chapter 2. Review of Bio-Amplifier Architectures -- Chapter 3. An Active Electrode Readout Circuit -- Chapter 4. An 8-Channel Active Electrode System -- Chapter 5. Current Noise of Chopper Amplifiers -- Chapter 6. A Digital Active Electrode System -- Chapter 7. Conclusions.
Keywords: Electronic circuits; Biomedical engineering; Electronics; Electronic Circuits and Systems; Biomedical Engineering and Bioengineering; Electronics and Microelectronics, Instrumentation